Tribological behavior of dual and triple particle size SiC reinforced Al-MMCs: a comparative study - Maleque, Md Abdul; Karim, Md Rezaul (EMERALD GROUP PUBLISHING LIMITED, 2008)
Purpose - The aim is to study the tribological behavior of dual particle size (DPS) and triple particle size (TPS) SiC reinforced aluminum alloy-based metal matrix composites - MMCs (Al/SiCp MMC).